The Effect of Motivation and Work Discipline on Employee Performance with Self-Efficiency as a Moderating Variable - Diansyah Diansyah; Hilda Juliani (Budapest International Research and Critics University, 2022)
A company cannot develop properly if it is not supported by quality human resources in the company, including by PT. BTS. The purpose of this study was to examine the effect of motivation and work discipline on employee performance with self-efficacy as a moderating variable. The research method used in this research is quantitative with Partial Least Square (PLS-SEM) technique and assisted by SmartPLS 3.0 software. The researcher chose the census technique in the sampling technique, namely all members of the population (All PT.BTS) were used as samples in this study to examine the moderating effect and the direct effect of the related variables. The results of this study indicate that there is an influence of motivation on employee performance, work discipline has no effect on employee performance, self-efficacy affects employee performance, self-efficacy is able to moderate motivation on performance and self-efficacy is able to moderate work discipline on employee performance. The method of determining the number of respondents' eligibility uses the Hair method which states that the respondent may be 5 to 10 times the number of research variable indicators.